Visual Syntax: how visual and verbal approach promote social unity through thematic television commercials - Khairulwafi Mamat,; Shahrunizam Sulaiman,; Hashima Mohaini Mohamad,; Safrina Muhamad Azmi,; Muhammad Nur Firdaus Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Commercials on television, in particular, have a significant impact on nation-building in addition to promoting products and services. Ads need to express ideas that extend beyond the bounds of the ads themselves, therefore they need captivating tales, unique ways of communicating with customers, and smart abstractions. By examining the effect of thematic television advertising by Petronas on social cohesion, this study provides a first step toward answering this question. Textual and visual aspects work together to generate a type of discourse in effective advertising, one that can influence a target audience's beliefs, values, expectations, and behaviours. Advertising permeates our daily lives and is rich with symbolic significance. Indeed, commercials, along with TV shows and films, serve as a catalyst to build and fortify national unity by spreading stories or ideas that stress the significance of appreciating and valuing Malaysia's many cultural traditions. The researchers set out to find examples of thematic television advertising that promotes societal togetherness through visual and verbal approaches, gestures, and graphic style. Three methods were used in this study; meta-analysis was used on the TVC, naturalistic observation was used on humans, and surveys were used to ask respondents some predetermined questions. The conceptual approach helped bring to light the significant visual attributes of communication media, especially TVC, in encouraging local audience members to accept and embrace the cultural differences present in Malaysia's diverse social landscape.